Analysis of genetic testing in fetuses with congenital heart disease of single atria and/or single ventricle in a Chinese prenatal cohort - Min Li; Baoying Ye; Yiyao Chen; Li Gao; Yi Wu; Weiwei Cheng (BMC, 2023)
Abstract Objective This study aimed to investigate the genetic etiologies of fetuses with single atria and/or ventricle (SA or/and SV) using different genetic detection methods in a Chinese prenatal cohort. Methods In this retrospective study, the various genetic results of 44 fetuses with SA and/or SV were analyzed. All 44 cases were tested by chromosomal microarray analysis (CMA) and karyotyping simultaneously, and 8 underwent whole exome sequencing (WES). Data on the pregnancy outcomes and neonatal prognoses were collected from medical records and postnatal follow-up. Results The whole cohort of 44 fetuses included 14 SA cases (31.8%), 12 SV cases (27.3%), and 18 SA and SV cases (40.9%). A total of 9 pathogenic genetic results were detected by conventional karyotyping, CMA and trio-WES, indicating an overall detection rate of 20.5% (9/44). Six pathogenic chromosomal abnormalities were identified by CMA among the 44 cases, showing a detection rate of 13.6% (6/44). Two microdeletions being missed by karyotyping were diagnosed by CMA, showing an additional diagnostic yield of 4.5% for CMA in present cohort(2/44). Three pathogenic variants in two fetuses were identified by WES, indicating an incremental diagnostic yield of 4.5%(2/44) for WES in fetuses with SA or/and SV. Conclusion In this study, WES achieved an additional diagnostic yield of 4.5% in fetuses with SA or/and SV. WES is valuable for fetal prognosis assessment and could add diagnostic value for fetuses with SA and/or SV when CMA is negative. It would be a valuable technique for the identification of underlying pathogenic variants in prenatal cohorts.